Pemetrexed Plus Lenalidomide for Relapsed/Refractory Primary Central Nervous System Lymphoma: A Prospective Single-Arm Phase II Study - Ma, Jingjing; Lin, Zhiguang; Ding, Tianling; Li, Qing; Zhang, Mengxue; Kang, Hui; Johnston, Patrick B.; Ma, Yan; Chen, Bobin (Frontiers in Oncology, 2022)
Abstract The prognosis of relapsed/refractory (R/R) primary central nervous system lymphoma (PCNSL) is dismal, and there are limited treatment options for these patients. This was a prospective single-arm phase II study of combined pemetrexed and lenalidomide for salvage treatment of R/R PCNSL. Patients with R/R PCNSL (n = 38) who had undergone two or more chemotherapy regimens and experienced disease progression or recurrence were enrolled. The primary endpoint was overall response rate (ORR). Secondary endpoints were progression-free survival (PFS) and overall survival (OS). Patients were followed up for a median of 18 (range, 1–36) months. ORR was 68.4%, with median PFS and OS of 6 and 18 months, respectively. Adverse events (AEs) included myelosuppression, fatigue, nausea, fever, infection, cardiac disease, and thrombogenesis. Commonly observed grade ≥ 3 AEs included neutropenia (5.3%), leukopenia (2.6%), thrombocytopenia (7.9%), and infection (2.6%). Elevated lactate dehydrogenase (LDH) levels (2 = 13.25; P = 0.0003) and bulky disease (P = 0.032; 2 = 4.580) were associated with short PFS. Elevated serum LDH level (P = 0.011; 2 = 6.560), abnormal lymphoma cells in the cerebrospinal fluid (CSF) [P = 0.011; 2 = 6.445], and multiple lesions (P = 0.036; 2 = 4.404) were significantly associated with poorer OS. Abnormal lymphoma cells in the CSF was an independent predictor of poor prognosis on multivariate analysis (P = 0.034; hazard ratio (HR) = 2.836; 95% confidence interval, 1.082–7.434). Our results indicate that pemetrexed plus lenalidomide is effective for heavily treated R/R PCNSL, with moderate toxicity. Trial registration: #ChiCTR1900028070.